Planning for Human Systems : Essays in Honor of Russell L. Ackoff - Snow, Roberta, 1955-; Choukroun, Jean-Marc; Ackoff, Russell Lincoln, 1919-2009 (Book collections on Project MUSE., 1992)
Russell Lincoln Ackoff is a recognized authority in the field of operations research and systems theory. This volume is divided into four major sections. The first deals with Ackoff's intellectual roots in the American pragmatic tradition. The second section demonstrates how systems thinkers have incorporated Ackoff's ideas in their own work. The third section shows the influence of Ackoff's thinking on decision making and problem solving, while the final section offers a reassessment of current approaches to systems planning on the national level. In addition, the editors have provided a general introduction, as well as introductions to each of the five sections. Planning for Human Systems will be of interest to students and scholars of operations research and systems theory. Contributors: Michel Chevalier, C. West Churchman, Thomas A. Cowan, Eric Trist, Ian I. Mitroff, Stafford Beer, and Ignacy Sachs.